Climate Change and Human Health: Systematic Literature Review on A Multidimensional Threat to Well-Being and Economic Stability - Teresiute, Paulina; Kaab Omeir, Ahmad; Meng, Wenting (Technium BioChemMed, 2025)
Climate change poses a multidimensional threat to human health and economic stability, with rising global temperatures, shifting precipitation patterns, and increased frequency of extreme weather events contributing to an escalating burden of disease worldwide. This systematic literature review and bibliometric analysis examine how climate change influences physical and mental health outcomes and evaluates the resulting economic consequences. Drawing on 377 peer-reviewed articles indexed in the Web of Science, the study employs a hybrid methodology combining quantitative bibliometric mapping using VOSviewer with qualitative content analysis. The findings reveal that climate-sensitive health conditions—including cardiovascular, respiratory, and vector-borne diseases—are becoming more prevalent, particularly in low- and middle-income countries. Moreover, climate-induced disruptions are linked to rising levels of anxiety, depression, PTSD, and eco-anxiety, disproportionately affecting vulnerable populations such as children, women, and socioeconomically disadvantaged groups. These health effects translate into significant economic costs through increased healthcare expenditures, loss of labour productivity, and long-term social instability. The co-occurrence network analysis highlights the evolution of research priorities toward governance, resilience, finance, and equity. The study concludes that addressing the climate-health-economic nexus requires integrated public health strategies, interdisciplinary collaboration, and the inclusion of mental health and economic risk indicators in climate adaptation policies. By placing human well-being at the core of climate discourse, the paper advocates for more holistic and inclusive responses to mitigate the compounding impacts of climate change.